2016
DOI: 10.1089/neu.2015.4041
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine Receptor Deficiency Is Associated with Early Protection but Late Worsening of Outcome following Brain Trauma in Mice

Abstract: An impaired ability to regulate microglia activation by fractalkine (CX3CL1) leads to microglia chronic sub-activation. How this condition affects outcome after acute brain injury is still debated, with studies showing contrasting results depending on the timing and the brain pathology. Here, we investigated the early and delayed consequences of fractalkine receptor (CX3CR1) deletion on neurological outcome and on the phenotypical features of the myeloid cells present in the lesions of mice with traumatic brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 65 publications
(84 reference statements)
3
73
0
Order By: Relevance
“…In recent years, it was reported that an M2-to-M1 microglia/macrophage switch occurs in spinal cord injury (Kigerl et al, 2009) and ischemic stroke (Hu et al, 2012), whereas a mixed M1 and M2 population is seen in traumatic brain injury (Morganti et al, 2016; Zanier et al, 2016). The microglial M1-to-M2 phenotype transition we observed in the ICH brain may result from phenotypic transformation of microglia in the early stage of ICH or result from M2-like microglial migration or M2-like macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it was reported that an M2-to-M1 microglia/macrophage switch occurs in spinal cord injury (Kigerl et al, 2009) and ischemic stroke (Hu et al, 2012), whereas a mixed M1 and M2 population is seen in traumatic brain injury (Morganti et al, 2016; Zanier et al, 2016). The microglial M1-to-M2 phenotype transition we observed in the ICH brain may result from phenotypic transformation of microglia in the early stage of ICH or result from M2-like microglial migration or M2-like macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, M2 microglia do have important functions in phagocytosis and toxicity clearance in other brain diseases 77 , such as ischaemic stroke 17,78 , TBI 79 and epilepsy 31 , suggesting that the function of M2 microglia in ICH should be explored.…”
Section: Microgliamentioning
confidence: 99%
“…A recent study by Zanier et al used CX3CR1 knockout mice to disrupt CX3CL1 chemokine signaling in order to understand its importance in controlling myeloid cell activity in TBI (50). After receiving a CCI injury, CX3CR1 knockout animals showed neurological protection 4 days following TBI.…”
Section: Involvement Of Immune Cell Types In Tbimentioning
confidence: 99%